Mitigating Corruption in Government Security Forces The Role of Institutions, Incentives, and Personnel Management in Mexico - Asch, Beth J. (RAND Corporation, 2011)
Mexico has undertaken reforms in recent years to professionalize its police. This report draws on the literature on corruption and personnel incentives and analyzes police reform in Mexico. It addresses the roots of corruption and the tools that could be used to mitigate it and provides an initial assessment of the reforms' effectiveness. The results suggest some progress, though police corruption still remains high and more work is needed.